Discovery of LY3325656: A GPR142 agonist suitable for clinical testing in human. Issue 5 (1st March 2020) - Liu, Lian Zhu; Ma, Tianwei; Zhou, Jingye; Long Hu, Zhi; Jun Zhang, Xue; Zhen Zhang, Hai; Zeng, Mi; Liu, Jia; Li, Lei; Jiang, Yi; Zou, Zack; Wang, Fan; et al.
Graphical abstract: Abstract: The discovery and optimization of a novel series of GPR142 agonists are described. These led to the identification of compound 21 (LY3325656), which demonstrated anti-diabetic benefits in pre-clinical studies and ADME/PK properties suitable for human dosing. Compound 21 is the first GPR142 agonist molecule advancing to phase 1 clinic trials for the treatment of Type 2 diabetes.